APLIKASI TRAVELLING SALESMAN PROBLEM PADA PENGEDROPAN BARANG DI ANJUNGAN MENGGUNAKAN METODE INSERTION - Priska Sari Dewi; Triyani Triyani; Siti Rahmah Nurshiami (Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2021)
Travelling Salesman Problem (TSP) is a problem to find the shortest path a salesman visitS all the cities exactly once, and return to the starting city. In this reseacrh, the methods for TSP used are the nearest insertion method, the cheapest insertion method, and the farthest insertion method. With help the function of Software R to creat a minimum TSP Program from three insertion methods.The TSP results for same number of point using three insertion methods do not always have the same weight and route but depending on the data used.